In silico antigenic site evaluation and antiviral therapy against dengue serotypes - Parida, Pratap; Deka, Priyadarshini; Shankar, Brajesh; Yadav, R. N. S. (Bangladesh Journal of Pharmacology, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> Nonstructural protein 3 (NS3) constitute protease, helicase and polymerase that are essential for dengue virus replication. The aim of the present study is to block the replication of the virus by targeting the NS3 Protein. The retrieved sequences of NS3 protein from National Centre for Biotechnology information (NCBI) shows that the antigenic sites of the protein are highly variable in all the four serotypes of dengue virus (DENV) i.e. DENV I, DENV II, DENV III and DENV IV. DENV III found to be most distantly related serotype among all the serotypes studied using UPGMA method. The 3D structure of NS3 protein was modeled using homology modeling by MODELLER 9v8. Evaluation of the constructed NS3 protein models were done by PROCHECK, WhatIf using Exome Horizon. The derived compounds of mycophenolic acid and ribavirin were docked as ligands to the constructed models of NS3 protein using Autodock 4.2 for Protein-ligand interaction study. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] -->